2022
DOI: 10.1186/s40478-022-01444-2
|View full text |Cite
|
Sign up to set email alerts
|

Tau seeding in cases of multiple sclerosis

Abstract: Relapsing remitting multiple sclerosis (MS) is an inflammatory demyelinating disorder of the central nervous system that in many cases leads to progressive MS, a neurodegenerative disease. Progressive MS is untreatable and relentless, and its cause is unknown. Prior studies of MS have documented neuronal accumulation of phosphorylated tau protein, which characterizes another heterogeneous group of neurogenerative disorders, the tauopathies. Known causes of tauopathy are myriad, and include point mutations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…According to post-mortem studies, tau hyperphosphorylation is found in the brain samples from patients with early aggressive, primary progressive, and secondary progressive MS, whereas the insoluble form is present only in cases of progressive MS [ 54 , 55 , 56 ]. It implies that the accumulation of phospho-tau protein may be the cause of progressive MS and it may be a secondary tauopathy [ 19 ]. In our study, the CSF was collected at the beginning of the disease and the majority of patients showed minimal disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to post-mortem studies, tau hyperphosphorylation is found in the brain samples from patients with early aggressive, primary progressive, and secondary progressive MS, whereas the insoluble form is present only in cases of progressive MS [ 54 , 55 , 56 ]. It implies that the accumulation of phospho-tau protein may be the cause of progressive MS and it may be a secondary tauopathy [ 19 ]. In our study, the CSF was collected at the beginning of the disease and the majority of patients showed minimal disability.…”
Section: Discussionmentioning
confidence: 99%
“…Although this pathological spreading of tau protein, also called seeding, was investigated in detail in tauopathies, mostly Alzheimer’s disease, recently it was also demonstrated in MS patients. LaCroix et al [ 19 ] showed tau seeding in the brain homogenates from six out of eight MS cases, suggesting tau may act as a mediator of neurodegeneration in MS.…”
Section: Introductionmentioning
confidence: 99%
“…In studies that examine cerebrospinal fluid biomarkers, changes in Aβ 42 as seen in AD can also predict early cognitive decline in MS [173]. Furthermore, the presence of tau seeding, which can lead to AD pathology [37, 98,100,102,105,[174][175][176], has been observed in the brains of patients with MS [177], and tau also may contribute to impaired oligodendrocyte maturation and pathological changes that may foster demyelination [178].…”
Section: Cognitive Loss and Dementia That Can Occur In Multiple Scler...mentioning
confidence: 99%
“…Finally, sex differences affect multiple body organs/functions, including, for example, the immune system. An interesting example is multiple sclerosis, an autoimmune disease, presenting tauopathy, being much more prevalent in women than men (LaCroix et al, 2022). Further touching the tip of this iceberg, microglial sex differences link with Tau‐related neurodegenerative diseases (Doust et al, 2021; see also above).…”
Section: More On Tau and Sexmentioning
confidence: 99%